DAX1/NR0B1 Was Expressed During Mammalian Gonadal Development and Gametogenesis Before It Was Recruited to the Eutherian X Chromosome. Issue 1 (1st January 2015) - Stickels, Robert; Clark, Kevin; Heider, Thomas N.; Mattiske, Deidre M.; Renfree, Marilyn B.; Pask, Andrew J.
Abstract: The nuclear receptor subfamily 0, group B, member 1 ( NR0B1 ) gene is an orphan nuclear receptor that is X-linked in eutherian mammals and plays a critical role in the establishment and function of the hypothalamic-pituitary-adrenal-gonadal axis. Duplication or overexpression of NR0B1 in eutherian males causes male to female sex reversal, and mutation and deletions of NR0B1 cause testicular defects. Thus, gene dosage is critical for the function of NR0B1 in normal gonadogenesis. However, NR0B1 is autosomal in all noneutherian vertebrates, including marsupials and monotreme mammals, and two active copies of the gene are compatible with both male and female gonadal development. In the current study, we examined the evolution and expression of autosomal NR0B1 during gonadal development in a marsupial (the tammar wallaby) as compared to the role of its X-linked orthologues in a eutherian (the mouse). We show that NR0B1 underwent rapid evolutionary change when it relocated from its autosomal position in the nonmammalian vertebrates, monotremes, and marsupials to an X-linked location in eutherian mammals. Despite the acquisition of a novel genomic location and a unique N-terminal domain, NR0B1 protein distribution was remarkably similar between mice and marsupials both throughout gonadal development and during gamete formation. A conserved accumulation of NR0B1 protein was observed in developing oocytes, where its function appears to be critical in the early embryo, prior to zygotic genome activation. Together these findings suggest that NR0B1 had a conserved role in gonadogenesis that existed long before it moved to the X chromosome and despite undergoing significant evolutionary change.